"Music is…"?! Significations attributed by middle school students to the notion of music. (December 2022) - Reis, Leandro Augusto dos; Oliveira, Francismara Neves de
This article presents the data of the significations attributed by students from the eighth year of Middle School to the notion of Music. Anchored in the Piagetian clinical–critical method and in the contribution of Genetic Epistemology, the research was carried out in a public school in the city of Londrina, Paraná, with the participation of 12 students. The results indicate that the notions of music are linked to the understanding of the social reality constructed by the participants. For this reason, by considering such constructive processes, through which social reality can be constantly signified by students, we aim to create opportunities for musical-pedagogical actions that favor the expansion of the idea of music and its domains.